PENERAPAN STRATEGI PEMBELAJARAN CRITICAL INCIDENT BERBANTUAN MEDIA GAMBAR SERIUNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR - Sahrani Taskia; Iis Aprinawati; Rizki Ananda; Muhammad Syahrul Rizal; Yenni Fitra Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low narrative writing skills of students in Indonesian language lessons in Grade III of SDN 006 Pasir Sialang. One solution to overcome this problem is the implementation of the Critical Incident learning approach assisted by serial picture media. The purpose of this study was to improve students’ narrative writing skills in Indonesian language lessons. The research method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of two meetings and four stages: planning, implementation, observation, and reflection. The research was carried out in August 2025. The subjects of this study were 15 third-grade students, consisting of 6 boys and 9 girls. Data collection techniques included observation, written test questions, and documentation. Prior to the implementation of the action, students’ narrative writing ability was 26.6%. In Cycle I Meeting I, it increased to 46.6%, and in Cycle I Meeting II it increased to 66.6%. Furthermore, in Cycle II Meeting I it increased to 80%, and in Cycle II Meeting II it increased to 93.3%. Thus, it can be concluded that the use of the Critical Incident learning strategy assisted by serial picture media can improve students’ narrative writing skills in Indonesian language subjects at SD 006 Pasir Sialang.